1988
DOI: 10.1007/bf02344746
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of fine roots of five tree species and maize in Morogoro, Tanzania

K. Jonsson,
L. Fidjeland,
J. A. Maghembe
et al.

Abstract: Abstract. In order to assess the possibility of root competition in agroforestry, the vertical distribution of fine roots (< 2 mm in diameter) of five tree species in pure two-year-old stands was compared to that of mature maize.Cassia siamea, Eucalyptus tereticornis, Leucaena leucocephala and Prosopis chilensis had a rooting pattern similar to that of maize, i.e. a slow decline in fine root mass from 0-100cm soil depth. Eucalyptus camaldulensis had its roots evenly distributed down to 100cm. On an average, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 8 publications
7
26
0
Order By: Relevance
“…Clumped distributions of tree roots within the soil, as seen in the proteoid roots of Grevillea robusta, might also reduce interspecific competition (Huxley et al, 1994). However, numerous studies have shown that most tree roots, especially those of fast-growing species, exploit the same soil depths as crop roots (Jonsson et al, 1988;Daniel et al, 1991;van Noordwijk et al, 1996), and the importance of root clumping remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Clumped distributions of tree roots within the soil, as seen in the proteoid roots of Grevillea robusta, might also reduce interspecific competition (Huxley et al, 1994). However, numerous studies have shown that most tree roots, especially those of fast-growing species, exploit the same soil depths as crop roots (Jonsson et al, 1988;Daniel et al, 1991;van Noordwijk et al, 1996), and the importance of root clumping remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, root abundance of leucaena declined with depth; however there was not greater abundance of fine roots in the top soil (0-1 m) as reported by other authors (Jonsson et al 1988;Dhyani et al 1990;Poole, 2003). In this study, many fine roots were observed between 1-2 m depth in the soil profile.…”
Section: Effect Of Within-row Density On Rooting Patternssupporting
confidence: 61%
“…It is assumed that there is spatial complementarity of use of the resources when trees and grass are combined, as tree roots can acquire water deeper in the soil strata (Cannel et al 1996). In a study of vertical root distribution of multipurpose tree species, Jonsson et al (1988) clarified the definition of "trees with deeper roots", because it is not clear if it infers that trees have most of their root biomass deep in the soil, or whether some roots reach deeper levels while the bulk of roots remain near to the surface. Clearly, in the Nelder fan experiment, leucaena had deeper root abundance than Rhodes grass suggesting a complementary use of water resources; however, the great abundance of fine roots of leucaena and Rhodes grass in the upper soil levels suggested a high level of competition for water resources.…”
Section: Complementarity and Competition For Water Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree root distribution can be used as an indicator of competition potential of trees, and high fine root concentrations of trees within crop root zone has been observed in previous studies involving fast growing trees (Jonsson et al 1988;Daniel et al 1991;Van Noordwijk et al 2015). Previous studies have shown that the concentration of fine tree roots decreases with distance from trees (Eastham and Rose 1990;Van Noordwikk et al 2015;Livesley et al 2000).…”
Section: Discussionmentioning
confidence: 95%